Sedimentary facies analysis of the Mesozoic clastic rocks in Southern Peru (Tacna, 18°S): Towards a paleoenvironmental Redefinition and stratigraphic Reorganization - Alván, Aldo (2018)
The Mesozoic rocks of southern Peru comprise a Middle Jurassic to Early Cretaceous sedimentary sequence deposited during a time interval of approximately 34 Myr. In Tacna, these rocks are detrital and constitute the Yura Group (Callovian to Tithonian) and the Hualhuani Formation (Berriasian). Basing on robust interpretation of facies and petrographic analysis, we reconstruct the depositional settings of such units and provide a refined stratigraphic framework. Accordingly, nine types of sedimentary facies and six architectural elements are defined. They preserve the record of a progradational fluvial system, in which two styless regulated the dispersion of sediments: (i) a high-to moderate-sinuosity meandering setting (Yura Group), and a later (ii) incipient braided setting (Hualhuani Formation). The Yura Group (Callovian-Tithonian) represents the onset of floodplain deposits and lateral accretion of point-bar deposits sited on a semi-flat topography. Nonetheless, the progradational sequence was affected by at least two rapid marine ingressions occurred during Middle Callovian and Tithonian times. Such marine ingressions reveal the proximity of a shallow marine setting and incipient carbonate deposition. In response to increase in topographic gradient, the Hualhuani Formation (Berriasian) deposited as extensive multistory sandy channels. The mineralogy of the Mesozoic sediments suggests sediment supplies and intense recycling from a craton interior (i.e. Amazon Craton and/or plutonic sources) located eastward of the study area.